The Strategic Role of Human Resource Management in Enhancing Occupational Health and Safety for Kindergarten Teachers - Evi, Selvianti; Sipatu, Lindanur; Rosida Adam; Wisra (Al-Qalam Institue, 2026)
This study aims to analyze the role of human resource management in enhancing Occupational Health and Safety (OHS) for teachers at Halimatul Sa’adiah Kindergarten, Malotong. Using a qualitative approach with a case study design, this research involved six informants comprising one principal and five teachers selected through purposive sampling. Data were collected via interviews, observations, and documentation, then analyzed using the Miles, Huberman, and Saldana interactive model assisted by NVivo 12 Plus software. The findings reveal that the implementation of OHS programs in the school is not yet optimal. Significant gaps exist in OHS planning, teacher training, evaluation, and leadership compliance. Furthermore, the safety and health of teachers are not fully guaranteed due to limited facilities, inadequate workspaces, and uneven health protection. These results imply an urgent need for school management to prioritize OHS policies through better budget allocation and infrastructure improvements. Establishing clear standard operating procedures and providing regular safety training are essential to ensuring that teachers can work in a secure environment, which ultimately sustains the quality of early childhood education